Pengaruh Pemberian Latihan Soal terhadap Motivasi Belajar dan Pengetahuan Pembuatan Celana Panjang Siswa SMK Negeri 1 Jabon Kelas XI Tata Busana: Penelitian - Dewita Rusdianti; Peppy Mayasari; Mita Yuniati; Lutfiyah Hidayati (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This research aims to demonstrate: (1) learning motivation, (2) knowledge of pant making, (3) the influence of providing practice questions on students' learning motivation, (4) the influence of providing practice questions on knowledge of making long pants, (5) the influence of providing practice questions on knowledge of making long pants moderated by learning motivation. The researcher used a quasi-experimental method with a nonequivalent control group design with a sample of two classes through purposive sampling techniques and instruments in the form of questionnaires and multiple-choice tests. The final results of the study show that students' learning motivation is at a high level in the control class at 71% and in the experimental class at 57%. Students' knowledge about making pants increased significantly after the treatment, where 89% of students in the experimental class achieved a good category compared to only 11% in the control class. Practice questions had an impact on improving students' knowledge, moderated by learning motivation, where highly motivated students showed optimal learning outcomes.